2016
DOI: 10.15690/vramn653
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the recombinant protein Tp0965 of Treponema pallidum as candidate antigen for serological diagnosis of syphilis

Abstract: Серологические методы сохраняют ведущее значение в лабораторной диагностике сифилитической инфекции [1]. Ежегодно в Российской Федерации проводится более 28 миллионов серологических исследований, по резуль-татам которых в 2015 году выявлено 34426 новых случаев данного заболевания. При этом, наряду с использовани-ем традиционных нетрепонемных тестов диагностики сифилиса, все более широкое распространение находят методы, основанные на обнаружении антител к создан-ным с использованием генной инженерии рекомбинант… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Tp0965 is a putative membrane fusion protein and belongs to efflux transporter resistance‐nodulation‐division family MFP subunit . Our and other previous study suggested that recombinant protein Tp0965 showed excellent antigenicity and immunoreactivity …”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Tp0965 is a putative membrane fusion protein and belongs to efflux transporter resistance‐nodulation‐division family MFP subunit . Our and other previous study suggested that recombinant protein Tp0965 showed excellent antigenicity and immunoreactivity …”
Section: Introductionmentioning
confidence: 59%
“…7 Our and other previous study suggested that recombinant protein Tp0965 showed excellent antigenicity and immunoreactivity. 10,11 Endothelial dysfunction plays key roles in vascular intimal inflammation by initiating the formation of atherosclerotic plaques and thrombosis. 12 It is also the key step of systemic dissemination and pathophysiological basic of syphilis.…”
Section: Introductionmentioning
confidence: 99%
“…Tp0965 is a putative membrane fusion protein and belongs to efflux transporter RND family MFP subunit [7]. Our and others previous study suggested that recombinant protein Tp0965 showed excellent antigenicity and immunoreactivity [10-11].…”
Section: Introductionmentioning
confidence: 99%